Efforts of the Guidance Teacher in Improving Elementary School Students' Ability to Analyze the Meaning and Recite Al-Asmaul Al-Husna through Audio-Visual Media - Zubaidah Zubaidah; Prio Utomo (Southeast Asian Journal of Global Trends and Issues in Education, 2025)
Background: The use of audio-visual media is highly effective in enhancing student engagement and comprehension, particularly in subjects that require both auditory and visual stimulation, such as analyzing and reciting al-asmaul al-husna. Objective: The primary objective of this study was to evaluate the impact of audio-visual media on improving the ability of fourth-grade students at SDN 36 Bengkulu Selatan to analyze the meaning and correctly recite al-asmaul al-husna. Method: This research was conducted as classroom action research in 2023 at SDN 36 Bengkulu Selatan. A total of 24 fourth-grade students participated in the study. The Minimum Completeness Criteria (KKM) were used to assess the students' learning progress over three cycles of intervention. Result: This study indicated a significant improvement in students’ ability to analyze and recite the al-asmaul al-husna. The average scores of the students increased progressively through each cycle, with the final cycle showing an 86.7% completion rate, surpassing the KKM threshold. Conclusion: The use of audio-visual media significantly enhanced the students’ ability to analyze the meaning and recite al-asmaul al-husna. This research demonstrates that well-designed media tools can enhance the quality of learning in religious education, suggesting that teachers adopt such tools to create more effective and engaging learning environments. Contribution: This study contributes to the growing body of research on the use of technology in religious education by providing empirical evidence of the positive effects of audio-visual media in teaching al-asmaul al-husna.